Teaching TEI: The Need for TEI by Example. - Terras, Melissa; Van den Branden, Ron; Vanhoutte, Edward (Literary & Linguistic Computing, 2009)
The Text Encoding Initiative (TEI)1 has provided a complex and comprehensive system of provisions for scholarly text encoding. Although a major focus of the 'digital humanities' domain, and despite much teaching effort by the TEI community, there is a lack of teaching materials available, which would encourage the adoption of the TEI's recommendations and the widespread use of its text encoding guidelines in the wider academic community. This article describes the background, plans, and aims of the TEI by Example project, and why we believe it is a necessary addition to the materials currently provided by the TEI itself. The teaching materials currently available are not suited to the needs of self directed learners, and the development of stand alone, online tutorials in the TEI are an essential addition to the extant resources, in order to encourage and facilitate the uptake of TEI by both individuals and institutions.